Analisis Pengambilan Keputusan Dan Kendala Dalam Penugasan Operasional Pada J&T Cargo Marapalam Padang - Awam Mukhatam Riziq; Ahmad Fatwa; Arif Hidayat; Bunga Henida Putri; Vivi Nila Sari (Pusat Riset dan Inovasi Nasional, 2024)
This community service aims to find out decision making and obstacles in operational assignments at J&T Cargo. Decision making is a result or output of a mental or cognitive process that leads to choosing a path of action among several available alternatives, each decision making result in a final choice. This is related to the assignment of position that have been determined by the leader in making a decision, then whether the decision can be carried out effectively according the employee’s abilities and knowledge. The aim of this research is to find out the decision making strategies and obstacles in operational assignments at J&T Cargo. This article was prepared by means of observation and interviews to collect data. The results of this research show that J&T Cargo is effective in making decision to obtain maximum work results in the future.